SMARCB1 mutations are not a common cause of multiple meningiomas. Issue 8 (14th May 2010) - Hadfield, K D; Smith, M J; Trump, D; Newman, W G; Evans, D G
Abstract : Background: Schwannomas and meningiomas are both part of the tumour spectrum of neurofibromatosis type 2 (NF2) and are associated with somatic loss of chromosome 22. They are also found commonly within the general population, unrelated to NF2. Germline SMARCB1 mutations have recently been identified as a pathogenic cause of a subset of familial schwannomatosis cases, and SMARCB1 is a candidate gene for causation of both schwannomas and meningiomas. Recently, Bacci et al reported a germline SMARCB1 mutation associated with familial schwannomatosis and multiple meningiomas. They concluded that SMARCB1 mutations can predispose to multiple meningiomas. Methods: We screened the SMARCB1 gene in a panel of 47 patients with multiple meningioma unrelated to NF2. Results: We found no germline mutations. Conclusion: We conclude that while meningiomas may be associated with the schwannomatosis phenotype, SMARCB1 is not a major contributor to multiple meningioma disease.